2016
DOI: 10.1016/j.jngse.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Gas storage and controlling factors in an over-mature marine shale: A case study of the Lower Cambrian Lujiaping shale in the Dabashan arc-like thrust–fold belt, southwestern China

Abstract: Lower Cambrian units in the upper Yangtze area of China are important strata for shale gas exploration. The Lower Cambrian Lujiaping shale in the Dabashan arc-like thrust-fold belt of the upper Yangtze area is thermally over-mature and has been transformed to slate by epimetamorphism. The Lujiaping shale has also experienced strong structural deformation; its current stratigraphic dip is 35°-80°. Over-maturity and strong deformation are considered unfavorable conditions for gas storage. However, desorption tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…OM pores are intraP pores that are found within OM, which are the most important storage space for shale gas, especially in over maturation marine shales in South China [10,32,62,72]. Organic matter pores in the LM shales can be commonly found on FE-SEM images ( Figure 5).…”
Section: Organic Matter Poresmentioning
confidence: 99%
“…OM pores are intraP pores that are found within OM, which are the most important storage space for shale gas, especially in over maturation marine shales in South China [10,32,62,72]. Organic matter pores in the LM shales can be commonly found on FE-SEM images ( Figure 5).…”
Section: Organic Matter Poresmentioning
confidence: 99%
“…The effects of in situ temperature and reservoir pressure on the adsorption capacity were also significant. Adsorption capacity decreasing with increasing temperature, while the opposite effect was the case with reservoir pressure (Han et al, 2016;Rexer et al, 2013). Free gas content is mainly controlled by in situ temperature and reservoir pressure, water saturation, and matrix porosity, and shows positive correlations with reservoir pressure and matrix porosity, while negative correlations are observed with temperature and water saturation .…”
Section: Introductionmentioning
confidence: 89%
“…Effects of mineral components on adsorption capacity. Previous studies have shown that minerals have significant impacts on the adsorption capacity (Han et al, 2016;Ji et al, 2015;Zhang et al, 2014). Clay and quartz minerals are the main mineral components in marine-terrigenous shale, with respective average values of 54.3% and 36.9%.…”
Section: Analysis Of Influencing Factors On Adsorption Capacitymentioning
confidence: 99%
“…Organic-rich shale currently produces commercial unconventional hydrocarbons and exhibits a wide variation in nano-and microscale geological attributes and geochemical properties [1][2][3][4][5]. The lower Cambrian Lujiaping Formation marine, organic-rich shales in the Dabashan Thrust-fold Belt of South China are being studied for their potential as shale gas reservoirs [6][7][8][9][10]. Several studies have discussed structural style and conditions of shale gas enrichment [6,10], while other studies have characterized microstructures and associated reservoir quality [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The lower Cambrian Lujiaping Formation marine, organic-rich shales in the Dabashan Thrust-fold Belt of South China are being studied for their potential as shale gas reservoirs [6][7][8][9][10]. Several studies have discussed structural style and conditions of shale gas enrichment [6,10], while other studies have characterized microstructures and associated reservoir quality [7][8][9]. Such investigations concentrate on nano-to microscale pore systems in the Lujiaping Shale using high-pressure methane sorption analysis, mercury injection capillary pressure (MICP), low-pressure nitrogen adsorption (LPNA), low-field nuclear magnetic resonance (NMR), and focused ion beam-scanning electron microscope imaging (FIB-SEM).…”
Section: Introductionmentioning
confidence: 99%